The Influence of Halaqah on Increasing Religiosity Members of the Student Activity Unit for Spirituality and Islamic Studies Ulul Albab University Islam Negeri Imam Bonjol Padang - Meidianas Saputra; Murisal Murisal; Mardenny Mardenny (Jurnal Syntax Admiration, 2023)
The purpose of this study was to test the religiosity possessed by students before being given halaqah, testing the religiosity possessed by students after being given halaqah, testing the differences in religiosity possessed by students before and after being given halaqa between the experimental group and the control group, proving the influence of halaqa to increase religiosity in students. This research uses an experimental method in the form of quasi-experimental design with a type of non-equivalent control group design. The population in this study amounted to 36 people, a sample of 18 people, nine people in the experimental group and nine people in the control group. Sampling in this study is systematic sampling. The data collection technique used in this study is a psychological scale, which is a scale of religiosity. The values of the pretest and posttetst were processed and compared using the independent sample T-test with the help of SPSS 16.00 for windows 2007.The results showed a significant difference between the experimental group given treatment in the form of halaqa with the control group that was not given treatment. Based on independent test sample T-test. Obtained Thit = 4.609 and Ttab = 2.120 at a significant level of 95% and α = 0.05. The alternative hypothesis is accepted because Thitung ≥ Ttabel, so it is proven that halaqah has an effect on increasing religiosity in T.A. 2017/2018 recruiting students of UKM KSI Ulul Albab UIN Imam Bonjol Padang.